Comparison of depression, anxiety, perceived stress, and resilience in parents faced with abortion in Iran: a longitudinal study - Zahra yazdanpanahi; Mahboubeh hajifoghaha; Alimohammad keshtvarz hesamabadi; Seyede Zahra Jafari (BMC Psychology)
Abstract Background Abortion could impact the mental well-being of parents. Resilience also has a significant effect on the mental health of the family as a factor in coping with abortion. This study aimed to compare depression, anxiety, perceived stress, and resilience in parents after abortion. Methods The present longitudinal study was performed on 200 hospitalized women and their spouses in the post-partum department of Shiraz hospitals in 2023. The instruments used in this study included questionnaires of fertility and demographic characteristics, hospital depression and anxiety (HADS), Connor’s resilience, and Cohen’s perceived stress. Data analysis was performed using SPSS 25. Results The mean age of the fathers was 35.37 ± 4.99 and that of mothers was 31.35 ± 6.23. The scores of parents’ anxiety, depression, and perceived stress in the first 24 h after facing abortion were in the highest possible state and decreased in 12 weeks, and their resilience also increased. In all three time periods, the mean scores of the fathers’ anxiety, depression, and perceived stress were lower than those of the mothers, but the mean score of resilience was always higher in fathers. Fathers´ age and mothers’ age, mothers’ age at the time of marriage, fathers’ job, number of children, gender of the last child (boy or girl), and unwanted pregnancy were among the predicting variables of anxiety, depression, perceived stress, and resilience of both parents faced with abortion. Conclusion Although mental disorders in fathers were fewer than mothers compared to post-abortion resilience, identifying and managing these issues promptly is crucial for enhancing post-abortion mental well-being in both parents. How parents navigate the challenges of pregnancy, childbirth, and abortion can significantly impact the couple’s health.